The epidemiology of polypharmacy in older adults: register-based prospective cohort study - Morin L (Clinical Epidemiology, 2018)
Lucas Morin,1 Kristina Johnell,1 Marie-Laure Laroche,2,3 Johan Fastbom,1 Jonas W Wastesson1 1Aging Research Center, Karolinska Institutet, Stockholm, Sweden; 2University Hospital of Limoges, Service de Pharmacologie, Toxicologie et Pharmacovigilance, Limoges, France; 3Faculté de Médecine, Université de Limoges, Limoges, France Objective: Polypharmacy is the concomitant use of several drugs by a single person, and it increases the risk of adverse drug-related events in older adults. Little is known about the epidemiology of polypharmacy at the population level. We aimed to measure the prevalence and incidence of polypharmacy and to investigate the associated factors. Methods: A prospective cohort study was conducted using register data with national coverage in Sweden. A total of 1,742,336 individuals aged ≥65 years at baseline (November 1, 2010) were included and followed until death or the end of the study (December 20, 2013). Results: On average, individuals were exposed to 4.6 (SD =4.0) drugs at baseline. The prevalence of polypharmacy (5+ drugs) was 44.0%, and the prevalence of excessive polypharmacy (10+ drugs) was 11.7%. The incidence rate of polypharmacy among individuals without polypharmacy at baseline was 19.9 per 100 person-years, ranging from 16.8% in individuals aged 65–74 years to 33.2% in those aged ≥95 years (adjusted hazard ratio [HR] =1.49, 95% confidence interval [CI] 1.42–1.56). The incidence rate of excessive polypharmacy was 8.0 per 100 person-years. Older adults using multi-dose dispensing were at significantly higher risk of developing incident polypharmacy compared with those receiving ordinary prescriptions (HR =1.51, 95% CI 1.47–1.55). When adjusting for confounders, living in nursing home was found to be associated with lower risks of incident polypharmacy and incident excessive polypharmacy (HR =0.79 and HR =0.86, p<0.001, respectively). Conclusion: The prevalence and incidence of polypharmacy are high among older adults in Sweden. Interventions aimed at reducing the prevalence of polypharmacy should also target potential incident polypharmacy users as they are the ones who fuel future polypharmacy. Keywords: drugs, older adults, polypharmacy, prescribing, medication, elderly